The Relationship Between Empowerment And Job Satisfaction on Employee Performance in Majalengka Regency - Ratna Ratna; Dewi Maharani (Procedia of Social Sciences and Humanities, 2021)
This study aims to see the relationship between empowerment and job satisfaction on employee performance in Majalengka Regency. This research uses a quantitative approach, with survey methods and path analysis techniques. The sample in this study were employees in the Majalengka environment with a sample size of 80 employees. The data collection technique in this research is by using a questionnaire containing several lists of statements. The results showed that (1) employee performance was directly affected by empowerment. Increased empowerment would result in an increase in performance of 3.2%. (2) Increased job satisfaction will result in an increase in employee performance by 19%. (3) job satisfaction is directly affected by empowerment, increasing empowerment will result in an increase in satisfaction by 12%.